The Clinical Presentation of Reversible Cardiomyopathy and Left Ventricular Noncompaction - A. Oshi; O. Abdelbasit; M. Z. Seidahmed; K. Hussein; A. Miqdad; M. Samadi; S. Alyousef; W. Manie; A. Farris; M. Abdullah (New Frontiers in Medicine and Medical Research Vol. 13, 2021)
This is a report of a female newborn baby who presented at the age of one hour after birth with signs of respiratory distress with marked cyanosis. The critical condition of the baby and the stormy course of the disorder highlighted the importance of starting immediate management and establishing an etiological diagnosis. Left ventricular noncompaction (LVNC) was eventually diagnosed in the baby and together with the metabolic management the baby survived the episode. This rare disorder of LVNC points to the importance of understanding the anatomical, physiological and metabolic processes which occur in the cardiac muscle to carry out its functions. Although LVNC has been described mostly in adults, more cases are now reported in children. However; cases with neonatal presentation of LVNC have been scarce in the literature. Hence it is important to report such cases because it provides the clue to uncover the etiological genetic disorders and familial occurrence.